Common variable immunodeficiency patients display elevated plasma levels of granulocyte activation markers elastase and myeloperoxidase - Litzman, Jiří; Chovancová, Zita; Bejdák, Petr; Litzman, Marek; Hel, Zdeněk; Vlková, Marcela (International journal of immunopathology and pharmacology, 2019)
Common variable immunodeficiency disorders (CVIDs) represent a group of primary immunodeficiency diseases characterized by hypogammaglobulinemia and dysfunctional immune response to invading pathogens. Previous studies have indicated that CVID is associated with microbial translocation and systemic myeloid cell activation. The goal of this study was to determine whether patients with CVID display elevated systemic levels of markers of granulocyte activation and whether the levels are further influenced by intravenous immunoglobulin (IVIg) infusions. The plasma levels of granulocyte activation markers elastase and myeloperoxidase were determined using enzyme-linked immunosorbent assay (ELISA) in 46 CVID patients and 44 healthy controls. All CVID patients were in a stable state with no apparent acute infection. In addition, granulocyte activation markers' plasma levels in 24 CVID patients were determined prior to and 1 h following IVIg administration. Neutrophil elastase and myeloperoxidase plasma levels were significantly higher in CVID patients than in healthy controls. Systemic elastase levels were further increased following IVIg administration. In vitro stimulation of 13 CVID patients' whole blood using IVIg in a therapeutically relevant dose for 2 h resulted in a significant increase in plasma elastase levels compared to unstimulated blood. The data presented here indicate that CVID is associated with chronic granulocytic activation which is further exacerbated by administering IVIg. Increased myeloperoxidase and elastase levels may contribute to associated comorbidities in CVID patients.
Keywords: Peroxidase; elastase; Humans; lidé středního věku; leukocytární elastasa; Immunoglobulins, Intravenous; běžná variabilní imunodeficience; Female; Aged; mladý dospělý; dospělí; peroxidasa; senioři; lidé; Biomarkers; Adult; biologické markery; ženské pohlaví; Male; immunoglobulin treatment; Middle Aged; neutrophil activation; Aged, 80 and over; Leukocyte Elastase; Young Adult; CVID; senioři nad 80 let; intravenózní imunoglobuliny; mužské pohlaví; myeloperoxidase; Common Variable Immunodeficiency